On‐Demand Continuous Flow Synthesis of Pentafluorosulfanyl Chloride (SF5Cl) Using a Custom‐Made Stirring Packed‐Bed Reactor - Peyrical, Lauriane C.; Mabit, Thibaud; Kairouz, Vanessa; Charette, André B. (Chemistry : a European journal, 2025)
The pentafluorosulfanyl (SF5−) group has been the subject of a surge of interest in the past decade, but there is still little practicality associated with its synthesis and installation. Herein is reported the first continuous flow synthesis of pentafluorosulfanyl chloride (SF5Cl), the most common reagent for the synthesis of SF5‐substituted compounds. The synthesis is based on inexpensive and easy‐to‐handle reagents: sulfur powder (S8), trichloroisocyanuric acid (TCCA) and potassium fluoride (KF). To this end, a custom‐made stirring reactor was designed to allow for fast, safe, and highly efficient on‐demand synthesis of SF5Cl. The resulting SF5Cl solution is showcased in the radical addition on alkynes in a telescoped fashion. Herein is reported the first continuous flow synthesis of pentafluorosulfanyl chloride (SF5Cl), the most widely used reagent for introducing the SF5 group onto aliphatic molecules. For this purpose, a custom‐made stirring reactor was designed and allowed rapid, safe and highly efficient synthesis of SF5Cl. Moreover, the following radical addition of SF5Cl on alkynes in a telescoped manner was realized.